IMPROVING STUDENTSâ€™ PRONOUNCING ABILITY USING PHONICS - Kurniati, Vivi; Wijaya, Bambang; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted to solve the problems that were the studentsâ€™ lack of reading in their first reading, and to find out whether the phonics technique can increase the studentâ€™s reading ability. The purposes of this research were: â€œTo obtain how well phonics to improve studentsâ€™ pronouncing abilityâ€ to the students of TK Kalam Kudus Pontianak. In this research, phonics is applied as one technique in order to increase young learnerâ€™s reading skill. Phonics is one strategy to help young children in pronouncing words or sentences to measure studentsâ€™ pronouncing ability. It is used to help students represent sound or sounds. For the young learners, it works as a guideline when they start reading, because they can ready a word or sentences but pronounce its sound. The method of this research was Classroom Action Research. The research was conducted in three cycles. Each of cycle consists of four stages that is planning, action, observing, and reflecting stage. The subject of this research was 15 students who are the students of Kindergarten B TK Kalam Kudus Pontianak. The finding proves that phonics technique is effective to improve the studentsâ€™ reading ability. The result of this research is the Kindergarten B students of TK Kalam Kudus Pontianak has shown their significant progress in improving reading by using phonics in each cycle: first cycle 1.4 point (very poor), second cycle 2.3 point (average) and third cycle 3.1 point (good). This means that phonics in one technique which is useful to improve studentsâ€™ reading skill.Keywords: Phonics, Young Learners, Pronouncing, Classroom Action ReseachÂ Â Â  Â  Â